Application of Neutrosophic Interval valued Goal Programming to a Supply Chain Inventory Model for Deteriorating Items with Time Dependent Demand - Sayan Chandra Deb; Sahidul Islam (Neutrosophic Sets and Systems, 2023)
A single deteriorating product’s EOQ model has been examined in the literature, where it is con sidered that the product deteriorate continuously but has a maximum lifespan. It has also been assumed that market demand is linearly related to time. Additionally, the credit-risk is required for the retailer to pay the purchase price is offered by the supplier. The total annual relevant cost has been demonstrated to be convex, suggesting that not only does the ideal replenishment cycle time exist, but that it is also singular. We identify the system’s ideal replenishment strategy, which reduces the overall cost per unit of time. To generalize the model we used Neutrosophic triangular numbers for the parameters. Finally, an numerical example is given to illustrate the theoretical results of this model.